THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND OWNERSHIP STRUCTURE ON COMPANY VALUE WITH PROFITABILITY AS MODERATOR - Haji, Sapto; Herawati, Vinola (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2025)
This study examines the effects of corporate social responsibility (CSR) disclosure quality and ownership structure on company value among Indonesian listed firms, with profitability serving as a moderating variable. The research addresses inconsistent findings in prior literature regarding CSR-value and ownership-value relationships by investigating whether financial performance conditions the effectiveness of these mechanisms. The study employs panel regression analysis on an unbalanced panel dataset comprising 612 non-financial firms listed on the Indonesia Stock Exchange, yielding 1,732 firm-year observations during 2022–2024. CSR disclosure is measured using a granular 0-to-3 scoring system based on the Global Reporting Initiative framework. Two model specifications are estimated: pooled ordinary least squares with sector and year fixed effects, and firm fixed-effects models, both utilizing clustered robust standard errors. CSR disclosure quality significantly enhances company value across both model specifications. Ownership structure demonstrates a significant positive effect in cross-sectional analysis but becomes insignificant under firm fixed-effects estimation. Profitability directly increases firm value and significantly strengthens the CSR-value relationship, functioning as a quasi-moderator. However, profitability does not moderate the ownership-value relationship, indicating that governance mechanisms operate independently of financial performance conditions. The three-year observation window may be insufficient to capture long-term CSR dynamics. Future research should employ extended longitudinal designs, decompose ownership into distinct components, and conduct cross-country comparative analyses to enhance generalizability. This study contributes a refined CSR measurement approach using a 0-to-3 disclosure quality scoring system, advancing beyond conventional dichotomous indices. The findings reveal that profitability selectively moderates stakeholder-oriented strategies (CSR) but not governance mechanisms (ownership), offering nuanced theoretical insights for emerging market contexts. Results provide practical guidance for managers integrating sustainability investments with financial performance strategies.